Communicating under stress and time pressure: foreign language teaching methodology - Nataliia Glushanytsia; Tetyana Tarnavska; Kateryna Shykhnenko; Olha Nahorna; Kateryna Palamarchuk; Maryna Vasylyeva-Khalatnykova; Kateryna Binytska; Dmytro Kostenko; Liudmyla Kucheriava (International Journal of Evaluation and Research in Education (IJERE), 2026)
The language-based miscommunication often has an emotional background, especially in non-standard situations, and leads to unintended consequences and even human losses. The analysis of English for specific purposes (ESP) curricula reveals the problem of insufficient attention paid to the development of professionally significant personality traits that determine the ability to avoid miscommunication. The research is based on the military context just because their mistakes might be fatal, but the fundamentals of the developed methodology can be applied to any ESP training. Case studies of language-based errors in military operations and behavioral observations to assess cadets’ emotional stability were used to develop the methodology. The study’s objectives were to identify factors affecting communication reliability in military operations and to propose methods for developing cadets’ professionally significant qualities that influence behavior under stress and time pressure. The article aims to present an English teaching methodology for the development of errorless communication skills. The novelty of this manuscript lies in its comprehensive and practice-oriented approach to military English teaching that integrates pedagogical methods with military simulation technologies, aligning instruction with NATO STANAG 6001 standards. The findings contribute to military language education and may serve as a model for similar high-stakes professional training environments.